Compliance of hazardous waste storage facilities at gas stations with hazardous waste management regulations - Innes Gi Sara Sara; Suyud Warno Utomo; Fatmah (Applied Environmental Science, 2026)
Background: Gas stations (SPBU) generate hazardous waste, including contaminated rags, used oil, waste batteries (accumulators), and electronic waste. Under Government Regulation No. 22 of 2021 on Environmental Protection and Management Implementation (PP 22/2021) and Regulation of the Minister of Environment and Forestry (PermenLHK) No. 6 of 2021, these wastes must be stored in Hazardous Waste Temporary Storage Facilities (TPS LB3). Previous studies have examined contamination risks and fire safety. However, limited studies have evaluated compliance with the updated TPS LB3 regulations. This study aims to analyze hazardous waste management and TPS LB3 availability at gas stations in DKI Jakarta. Methods: This study uses quantitative descriptive methods complemented by qualitative analysis (mixed methods). The sample comprised nine purposively selected gas stations in DKI Jakarta. Data were collected through questionnaires, field observations, and interviews with gas station operators and managers, then analyzed using a checklist based on the technical specifications of PermenLHK No. 6 of 2021. Findings: Among nine gas stations, three (33.3%) had TPS LB3, while six (66.7%) did not. Compliance with the regulation reached 78.9%; however, no station met the permanent building requirement, and only 33.3% implemented hazardous waste logbook documentation. Gas stations without TPS LB3 achieved only 26.9% compliance. Conclusion: TPS LB3 implementation at gas stations in DKI Jakarta generally does not comply with PermenLHK No. 6 of 2021. The main deficiencies involve permanent buildings, drainage systems, and hazardous waste documentation. Novelty/Originality of this article: This study provides empirical evidence of compliance gaps in TPS LB3 implementation under Indonesia's updated hazardous waste regulations, identifying priority aspects for improving hazardous waste management at gas stations.